2013 Ieee Conference on Information and Communication Technologies 2013
DOI: 10.1109/cict.2013.6558160
|View full text |Cite
|
Sign up to set email alerts
|

Performance analysis of diverse environment based on RSSI localization algorithms in wsns

Abstract: Wireless sensor networks (WSNs) are widely used in many environments and adverse terrains. Location estimation of sensor nodes is still a crucial area of research because of new localization requirements. One of the main hurdles facing sensor localization in WSNs is accuracy. Many localization algorithms and techniques have been proposed to estimate the position of nodes. In this paper, we consider an RSSI (received signal strength indicator) range based localization algorithm that relies on measuring the rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…The trilateration measurement method [17][18][19][20] is widely used for positioning the calculation of sensor nodes in WSNs. This method can be used to determine the sensor node position if the distance between the three anchor nodes and target sensor node are known [7].…”
Section: Related Workmentioning
confidence: 99%
“…The trilateration measurement method [17][18][19][20] is widely used for positioning the calculation of sensor nodes in WSNs. This method can be used to determine the sensor node position if the distance between the three anchor nodes and target sensor node are known [7].…”
Section: Related Workmentioning
confidence: 99%
“…Xu et al [28] proposed an RSSI-based distance measurement model using log-normal shadowing model with dynamic variance propagation model and found that the proposed propagation model owns strong self-adaptability to various environments. Livinsa and Jayashri [29] proposed an RSSI-based location algorithm for distance estimation and location estimation under outdoor environment and indoor environment. They discovered that the performance of distance estimation in outdoor environment is better than that in indoor environment.…”
Section: Related Workmentioning
confidence: 99%
“…Localization is motivated by military applications such as battlefield surveillance. In localization, there are various algorithms and techniques that have been proposed for a localize node [11]. Mainly localization uses two types of nodes namely anchor node or beacon node and target node or unknown node [9] [10].…”
Section: Background Of Localizationmentioning
confidence: 99%
“…Z.Mary Livinsa el at [11] proposed the RSSI based localization algorithm for distance estimation and position estimation for reduce the localization error. In distance estimation, path loss model is used for the received signal strength power and 3 anchor nodes are used for the position estimation with trilateration method to reduce the localization error by using linear equation.…”
Section: Multilaterationmentioning
confidence: 99%